Biomechanical Comparison of Five Posterior Cruciate Ligament Reconstruction Techniques - Nuelle, Clayton W.; Milles, Jeffrey L.; Pfeiffer, Ferris M.; Stannard, James P.; Smith, Patrick A.; Kfuri, Mauricio, Jr.; Cook, James L. (The Journal of Knee Surgery, 2017)
No surgical technique recreates native posterior cruciate ligament (PCL) biomechanics. We compared the biomechanics of five different PCL reconstruction techniques versus the native PCL. Cadaveric knees (n = 20) were randomly assigned to one of five reconstruction techniques: Single bundle all-inside arthroscopic inlay, single bundle all-inside suspensory fixation, single bundle arthroscopic-assisted open onlay (SB-ONL), double bundle arthroscopic-assisted open inlay (DB-INL), and double bundle all-inside suspensory fixation (DB-SUSP). Each specimen was potted and connected to a servo-hydraulic load frame for testing in three conditions: PCL intact, PCL deficient, and PCL reconstructed. Testing consisted of a posterior force up to 100 N at a rate of 1 N/s at four knee flexion angles: 10, 30, 60, and 90 degrees. Three material properties were measured under each condition: load to 5 mm displacement, maximal displacement, and stiffness. Data were normalized to the native PCL, compared across techniques, compared with all PCL-intact knees and to all PCL-deficient knees using one-way analysis of variance. For load to 5 mm displacement, intact knees required significantly (p < 0.03) more load at 30 degrees of flexion than all reconstructions except the DB-SUSP. At 60 degrees of flexion, intact required significantly (p < 0.01) more load than all others except the SB-ONL. At 90 degrees, intact, SB-ONL, DB-INL, and DB-SUSP required significantly more load (p < 0.05). Maximal displacement testing showed the intact to have significantly (p < 0.02) less laxity than all others except the DB-INL and DB-SUSP at 60 degrees. At 90 degrees the intact showed significantly (p < 0.01) less laxity than all others except the DB-SUSP. The intact was significantly stiffer than all others at 30 degrees (p < 0.03) and 60 degrees (p < 0.01). Finally, the intact was significantly (p < 0.05) stiffer than all others except the DB-SUSP at 90 degrees. No technique matched the exact properties of the native PCL, but the double bundle reconstructions more closely recreated the native biomechanics immediately after implantation, with the DB-SUSP coming closest to the native ligament. This study contributes new data for consideration in PCL reconstruction technique choice.
Keywords: posterior cruciate ligament; autograft; allograft; reconstruction techniques; biomechanics